Peran Polri Dalam Penanggulangan Tindak Pidana Pencurian Kendaraan Bermotor Oleh Anak Di Daerah Bangkalan - Khoirul Abror; M. Syahrul Borman; Wahyu Prawesti; Dudik Djaja Sidarta (JOURNAL OF SHARIA ECONOMICS, 2022)
Motor vehicle theft by children is a criminal phenomenon that causes social unrest and raises legal issues related to child protection. This study aims to analyze the factors causing children to commit motor vehicle theft in the Bangkalan area and examine the role of the Indonesian National Police in combating this crime. This study uses an empirical legal approach with qualitative methods through interviews, observations, and document studies. The results show that economic factors, family disorganization, social environmental influences, low legal education, and weak supervision are the main determinants of child involvement in criminal acts. In the context of countermeasures, the Indonesian National Police implements preventive, repressive, and restorative justice strategies in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Rehabilitative and diversion approaches are the main instruments in maintaining a balance between law enforcement and the protection of children's rights.